THE ROLE OF ACUPUNCTURE THERAPY TO OVERCOME ONE-SIDE HEAD PAIN (MIGRAINE) - Mainnah, Mut; Septriana, Maya; Wurlina, Wurlina (Faculty of Vocational Studies, Universitas Airlangga, 2022)
Background: Migraine is a primary headache, usually described as pain attacks lasting 4 - 72 hours, unilateral, throbbing, with moderate to severe pain intensity that can be exacerbated by activity, and can be accompanied by nausea and vomiting, photophobia and phonophobia. Migraine can interfere with patient activities, so that it can reduce productivity and result in an economic burden to the family and reduce the patient's quality of life. To handle it, pharmacological and non-pharmacological therapies can be used. Acupuncture therapy is one of the non-pharmacological therapeutic options that can be used in migraines. Purpose: This article review collects and analyzes journals related to the effect of acupuncture therapy on migraines. The journal search method was carried out electronically from December to April 2021 using several databases such as Pubmed, Sagepub and Google Schoolar with the keywords: acupuncture in cases of migraine, acupuncture for migraine, and acupuncture point for migraine. Review: The journal searches discovered that acupuncture therapy had an effect in reducing pain intensity in migraine cases with the most widely used method that was the manual acupuncture method. However, the most influential method was the combination method of manual acupuncture, herbal acupuncture, and nutritional therapy with the hyperactivity of Yang liver as the frequently occurring syndrome. The frequently used points were the acupuncture points of Fengchi-GB20, Hegu-LI4, Taichong-LR3, Baihui-DU20, Zusanli-ST36, Sanyinjiao-SP6, and Taiyang-EX-HN5.Conclusion: Based on the journal analyses, the combination method of manual acupuncture, herbal acupuncture, and nutritional therapy can reduce pain intensity in migraine cases